Characterization of renewable reductants and charcoal-based pellets for the use in ferroalloy industries. (15th January 2019) - Surup, Gerrit; Vehus, Tore; Eidem, Per-Anders; Trubetskaya, Anna; Nielsen, Henrik Kofoed
Abstract: This study investigates the effect of high-temperature pyrolysis and post-treatment processes on spruce and oak charcoal yields and CO2 reactivity in a slow pyrolysis reactor. Post-treatment processes such as co-pyrolysis of biomass and recirculated tar mixture with that to the distillation of the charcoal-tar blend gave similar increase in charcoal yields. From a technological standpoint, co-pyrolysis of charcoal and tar mixture decreased the CO2 reactivity of the charcoal approaching that of fossil-based coke. This emphasize the importance of tar addition and high temperature treatment on charcoal properties. Moreover, the findings of this work show the potential use of the tar organic fractions as a binder that can be used for the charcoal pellet preparation. The results are promising as they show that the charcoal-based pellets have comparable properties of pellets from herbaceous biomass leading to the cost reduction in charcoal transportation and storage. Highlights: The heat treatment temperature had the highest influence on char yield. Co-pyrolysis of pinewood char with tar decreased the char reactivity. Co-pyrolysis with tar and distillation increased the char yield significantly. Tar addition to charcoal pellets improved hardness and electrical resistance.